Pemberdayaan Guru Sekolah Inklusif Melalui Implementasi Ai Literacy Untuk Mendukung Pembelajaran Adaptif Bagi Siswa dengan Hambatan Intelektual - Rizqi Fajar Pradipta; Dimas Arif Dewantoro; Wiwik Dwi Hastuti (JURPIKAT, 2026)
Inclusive education requires teachers to design responsive learning to the diverse needs of students, including those with intellectual disabilities. This community service activity aims to improve the artificial intelligence (AI) literacy of inclusive school teachers as a basis for developing adaptive learning. The activity was implemented through needs analysis, outreach, module development, training, implementation assistance, and evaluation and reflection. The material refers to the four domains of AI literacy: recognizing, utilizing, managing, and reflecting on AI. The activity results showed improved teacher competency in understanding AI, developing adaptive materials, using AI tools, implementing ethics, maintaining data security, and conducting differentiated assessments. The mentoring also increased teacher confidence and preparedness.